2022
DOI: 10.1186/s13036-022-00296-7
|View full text |Cite
|
Sign up to set email alerts
|

An ensemble-based drug–target interaction prediction approach using multiple feature information with data balancing

Abstract: Background Recently, drug repositioning has received considerable attention for its advantage to pharmaceutical industries in drug development. Artificial intelligence techniques have greatly enhanced drug reproduction by discovering therapeutic drug profiles, side effects, and new target proteins. However, as the number of drugs increases, their targets and enormous interactions produce imbalanced data that might not be preferable as an input to a prediction model immediately. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Representation learning based methods aim to improve the DTI prediction performance by extracting a rich feature of drugs and targets. Recent trends include combining different representations ( El-Behery et al 2022 , Khojasteh et al 2023 ) or modelling the feature with multimodalities ( Xia et al 2023 ) to further boost the performance. However, several studies have demonstrated that representation learning-based models often attain high prediction accuracy by overfitting specific representational features ( Bai et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Representation learning based methods aim to improve the DTI prediction performance by extracting a rich feature of drugs and targets. Recent trends include combining different representations ( El-Behery et al 2022 , Khojasteh et al 2023 ) or modelling the feature with multimodalities ( Xia et al 2023 ) to further boost the performance. However, several studies have demonstrated that representation learning-based models often attain high prediction accuracy by overfitting specific representational features ( Bai et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%